Estudo hidrogeoquímico e vulcanológico de lagos no arquipélago dos Açores : aplicações para a mitigação de riscos naturais - Antunes, Paulo Custódio Pires (2009)
The hydrogeochemical monitoring of volcanic lakes is a recent area of study when compared with other techniques which are more commonly applied to mitigation of hazards associated to active volcanoes. The research on these surface water bodies for monitoring in volcanology results from the behavior of lakes as condensers of volcanic fluids. Sometimes volcanic lakes even accumulate extremely acidified fluids due to condensation of these fluids. The largest Azorean lakes are emplaced inside volcanoes and some of these structures are active. The hydrogeochemical characterization of these lake waters and the study of the interaction with volcanic fluids can give a better understanding of systems. Therefore, the main objective of the present work is the characterization of volcanic lakes in the Azores and to forecast the possibility to use these aquatic systems for volcanic surveillance. The lake locations in the vicinity of populated areas emphasize the need for a better knowledge of the systems. The recent history on the Azores, reported some volcanic eruptions that have taken place within volcanic lakes or near and these eruptive events are responsible by changes on the lakes. In order to fulfill the main objective of this thesis several lakes were selected in São Miguel, Terceira, Graciosa, Pico, Flores and Corvo islands. At these lakes, corresponding to diverse volcanological settings, sampling was periodically made along the water column. The water analyses were carried out at the Hydrogeochemistry laboratory of the Geosciences Department of the Azores University. Water samples from several lakes were also sent to Activation Laboratories (Canada) to determine the major, minor and trace elements content. The isotopes 2H, 18O, 13C and 34S was made in the Stable Isotope Laboratory of the Mineralogy and Geochemistry Institute (University of Lausanne, Switzerland). All data collected was organized in digital form to make a database that is entitle DataLake. Specific hydrogeochemical software was used in order to proceed to data interpretation. Simulations with the model DYSREM_CAEDYM were conducted to study the behavior of same lakes as a response to an input of a inorganic CO2-water rich source. The results of these simulations have contributed to understand the possibility of significant increases of CO2 concentration in lake waters due to volcanic fluids contamination. Therefore, the model suggests that the contribution from organic free CO2, due to an organic matter degradation source, is not able to explain the total concentration of CO2 in some of the studied lakes. The exceeding CO2 can be due to interaction with volcanic fluids. The data also suggests that water chemistry on the studied lakes is influenced by salt contamination due to atmospheric transportation. However, same lakes appear to have the influence of other chemical modifying processes, such as the water-rock interaction or even the interaction with fluids of volcanic origin. From all the studied lakes, Furna do Enxofre (Graciosa island) shows higher concentrations in the analyzed species resulting from the volcanic contamination.